2020
DOI: 10.1021/acs.inorgchem.0c01581
|View full text |Cite
|
Sign up to set email alerts
|

TAML- and Buffer-Catalyzed Oxidation of Picric Acid by H2O2: Products, Kinetics, DFT, and the Mechanism of Dual Catalysis

Abstract: Studies of the oxidative degradation of picric acid (2,4,6trinitrophenol) by H 2 O 2 catalyzed by a fluorine-tailed tetraamido macrocyclic ligand (TAML) activator of peroxides [Fe III {4,5-Cl 2 C 6 H 2 -1,2-(NCOCMe 2 NCO) 2 CF 2 }(OH 2 )] − (2) in neutral and mildly basic solutions revealed that oxidative degradation of this explosive demands components of phosphate or carbonate buffers and is not oxidized in their absence. The TAML-and buffer-catalyzed oxidation is subject to severe substrate inhibition, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
4
5
0
Order By: Relevance
“…Conversely, H 2 PO 4 – is moving away from the first coordination sphere, leaving the option for a weak interaction within the second coordination sphere. Such a scenario has been considered in detail in our previous work . In our opinion, this experiment presents even stronger evidence for a higher affinity of HPO 4 2– versus H 2 PO 4 – toward Fe III of TAML 1 .…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Conversely, H 2 PO 4 – is moving away from the first coordination sphere, leaving the option for a weak interaction within the second coordination sphere. Such a scenario has been considered in detail in our previous work . In our opinion, this experiment presents even stronger evidence for a higher affinity of HPO 4 2– versus H 2 PO 4 – toward Fe III of TAML 1 .…”
Section: Resultssupporting
confidence: 54%
“…For the prototype TAML activator, 2a , protons and general acids , at appropriate concentrations cause Fe III ejection with liberation of the corresponding macrocyclic ligand. General acids such as mono- and dihydrogen phosphate are often components of buffer solutions in which the catalytic activity of TAMLs is explored. , On rare occasions, TAML catalysis is not observed in the absence of phosphate ions; i.e., phosphate can be more than a pH controller and also serves as a promoter of catalysis. Thus, in building an extensive understanding of the catalytic cycle, it is important to understand the effects of phosphate on the latest generation of TAML activators, among which 1 is the optimal performer thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to our system, the non-innocent role of the phosphate and sodium carbonate-bicarbonate (CO 2− 3 /HCO − 3 ) buffers has been established in the H 2 O 2 oxidative decomposition of various aromatic pollutants, catalyzed by iron(III) tetrasulfophthalocyanine [37] and iron(III) TAML complexes [38]. In the latter case, it was clearly revealed that picric acid was not oxidized in their absence.…”
Section: Catalytic Oxidation Of Morinsupporting
confidence: 68%
“…42 2.6. (6,12,20,30,40,60,120,240, and 360 min) using five treatment conditions (three separate experiments for each condition set and time) with two H 2 O 2 control conditions (1 h heat map in Figure 2; for other times, see Figure S1). The 2/ H 2 O 2 MPPRs were then analyzed to determine the conditions that best balance technical and likely cost performances and are compared with those of ozone (2 and 4 ppm) on the same water in Figure 2 and with higher ozone concentrations (6 and 8 ppm) (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…TAML catalysts (Figure ) are bioinspired, miniaturized replicas (typically <1% by mass) of the peroxidase enzymes that faithfully mimic the efficient enzymatic catalytic cycle . The latest-generation TAMLs (e.g., 2 is the current best overall technical performer) outperform their predecessors (e.g., 1 ), which have been previously shown to activate peroxide to effectively degrade MPs, including pharmaceuticals, pesticides, natural and synthetic estrogens and testosterone, antimicrobials, bacterial spores, explosives, , dyes, , industrial chemicals including bisphenol A, and many more. , In a study on wastewater samples from a London Municipal Wastewater Treatment Plant (MWWTP), the highest-performance earlier-generation TAML system, 1 (40 and 80 nM) with H 2 O 2 (20 ppm), impressively degraded 11 priority MPs of the U.K. water industry present initially in parts per trillion to low parts per billion concentrations . However, 1 is an organofluorine catalyst.…”
Section: Introductionmentioning
confidence: 99%